Oxygen orders differently under graphene: new superstructures on Ir(111). Issue 4 (1st October 2015) - Martínez-Galera, A. J.; Schröder, U. A.; Huttmann, F.; Jolie, W.; Craes, F.; Busse, C.; Caciuc, V.; Atodiresei, N.; Blügel, S.; Michely, T.
Abstract : New arrangement of oxygen adatoms chemisorbed on Ir(111) induced by the graphene cover. Abstract : Using scanning tunneling microscopy, the oxygen adsorbate superstructures on bare Ir(111) are identified and compared to the ones formed by intercalation in between graphene and the Ir(111) substrate. For bare Ir(111) we observe O-(2 × 2) and O-(2 × 1) structures, thereby clarifying a persistent uncertainty about the existence of these structures and the role of defects for their stability. For the case of graphene-covered Ir(111), oxygen intercalation superstructures can be imaged through the graphene monolayer by choosing proper tunneling conditions. Depending on the pressure, temperature and duration of O2 exposure as well as on the graphene morphology, O-(2 × 2), O-(√3×√3)-R30°, O-(2 × 1) and O-(2√3 × 2√3)-R30° superstructures with respect to Ir(111) are observed under the graphene cover. Two of these structures, the O-(√3 × √3)-R30° and the (2√3 × 2√3)-R30° structure are only observed when the graphene layer is on top. Phase coexistence and formation conditions of the intercalation structures between graphene and Ir(111) are analyzed. The experimental results are compared to density functional theory calculations including dispersive forces. The existence of these phases under graphene and their absence on bare Ir(111) are discussed in terms of possible changes in the adsorbate-substrate interaction due to the presence of the graphene cover.